PERANCANGAN APLIKASI MODUL PEMBERITAHUAN EKSPOR BARANG MELALUI ATAU DARI PUSAT LOGISTIK BERIKAT BERBASIS JAVAFX - Sri Lestari; Dona Hayatul Nurmikdar (CKI ON SPOT, 2021)
The writing of this document is intended for guidance and documentation of all activities that will be carried out during the development of desktop-based software, which within the scope of DJBC IT is called a module, starting from the user requirement stage, analysis and design, implementation to testing. The purpose of developing this module is to automate the implementation of the export of goods through or from the Bonded Logistics Center (PLB) or what is often referred to as BC3.3. This BC3.3 module is used by Exporters who have registered in the Permit Decree as Organizers of Bonded Logistics Centers and Entrepreneurs in the Bonded Logistics Center. The form of automation carried out includes the making of BC3.3 documents, sending data to the DJBC server and retrieving responses, along with other functions that are used to support the document making process BC3.3. This writing is said to be successful if the module in question can handle all user needs and business processes listed in this document.